Pleomorphic adenoma of the lacrimal gland in a developing community - B. Onuigboa, W.I.; O. Magulike, N. (Scientific Journal of Medical Science, 2013)
This study presents cases of lacrimal gland pleomorphic adenoma (LGPA) diagnosed postoperatively in a developing community. Records kept at a Reference Pathology Laboratory serving the Igbo Ethnic Group in Nigeria were searched for positive cases of LGPA which occurred between 1976 and 1990. Seven cases submitted by individual ophthalmologists were not preoperatively diagnosed as pleomorphic adenoma but as tumour, haemangioma, cyst, fibroma, adenocarcinoma and squamous cell carcinoma. The ages ranged from 17 years to 55 years (mean 34 years). The male:female ratio was 3:4 and the right:left ratio came to 5:2. The symptoms were diplopia, proptosis, and swelling. The duration before presentation varied from I year to 15 years. Five lesions were in the orbital lobe and 2 in the palpebral lobe. The excised mass measured a maximum diameter of 2 to 4 cm (mean 3 cm). In this developing community, where LGPA was not preoperatively diagnosed, recourse to histopathology put this interesting entity on the epidemiology map of the world.